2021
DOI: 10.1016/j.waojou.2021.100542
|View full text |Cite
|
Sign up to set email alerts
|

How are patients with chronic urticaria interested in using information and communication technologies to guide their healthcare? A UCARE study

Abstract: Background Patients with chronic urticaria (CU) are increasingly using information and communication technologies (ICTs) to manage their health. What CU patients expect from ICTs and which ICTs they prefer remains unknown. We assessed why CU patients use ICTs, which ones they prefer, and what drives their expectations and choices. Methods In this cross-sectional study, 1841 patients across 17 countries were recruited at UCAREs (Urticaria Centers of Reference and Excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In the recent Urticaria Centers of Reference and Excellence (UCARE) study, chronic urticaria information and communication technologies (CURICT), we assessed use and interest in information and communications technologies (ICTs) for patients with chronic urticaria (CU). 1 , 2 We found that almost all CU patients had access to ICTs and most were using these regularly to obtain health and disease‐related information. 1 Specifically, most patients with CU were interested in ICTs to receive disease information and to communicate with their physicians and other patients about their urticaria.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…In the recent Urticaria Centers of Reference and Excellence (UCARE) study, chronic urticaria information and communication technologies (CURICT), we assessed use and interest in information and communications technologies (ICTs) for patients with chronic urticaria (CU). 1 , 2 We found that almost all CU patients had access to ICTs and most were using these regularly to obtain health and disease‐related information. 1 Specifically, most patients with CU were interested in ICTs to receive disease information and to communicate with their physicians and other patients about their urticaria.…”
Section: Introductionmentioning
confidence: 86%
“…The scope, methodology, conduct, and other results of the CURICT study have been previously reported. 1 , 2 Patients were ≥12 years old and previously diagnosed with chronic spontaneous urticaria (CSU) or chronic inducible urticaria (CIndU) by a physician; those with other dermatological diseases or intellectual disabilities were excluded. A 23‐item questionnaire, designed, evaluated, and reviewed by an expert panel of physicians that collected demographic (age, gender, education level, living area, etc) and clinical information (urticaria type, years with diagnosis, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations